The Influence of Physical Activity on the Quality of Life of Cervical Cancer Patients Undergoing Chemotherapy Treatment - Dwi Kurniasih; Elisabeth Wahyu Savitri; Yusta Angelina (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Cervical cancer is one of the most common types of cancer experienced by women worldwide. During treatment procedures such as chemotherapy and radiotherapy, patients often face challenges in the recovery process, both physically and emotionally, which may lead to a decline in their quality of life. One of the ways to support reproductive health recovery is through physical activity, as it can improve blood circulation and help regulate hormonal balance. This study aims to analyze the effect of physical activity on the quality of life of cervical cancer patients undergoing chemotherapy.Subjects and Method: This is a cross-sectional study conducted at Dr. Soedarso Hospital, Pontianak, West Kalimantan. A total of 30 cervical cancer patients undergoing chemotherapy were selected in this study. The dependent variable was quality of life. The independent variable was physical activity. Data were collected by questionnaire and analyzed using Spearman rho test.Results: Spearman's rho correlation analysis showed a strong and statistically significant relationship between physical activity and quality of life in cancer patients (r = 0.66; p < 0.001). These results indicate that higher levels of physical activity improve the quality of life in cervical cancer patients.Conclusion: The findings demonstrate a strong and significant relationship between physical activity and the quality of life of cervical cancer patients. This indicates that the better the physical activity performed, the better the quality of life of cervical cancer patients.